Determinants of green consumption: a systematic literature review using the TCCM approach - Megha, (Frontiers in Sustainability, 2024)
Introduction Over the past decade, there has been growing research into the consumption of environmentally friendly products, driven by heightened environmental concerns and a shift towards more conscientious purchasing. Despite generally favorable attitudes towards green products, actual purchase rates remain low, creating a gap between attitudes and behavior. Existing studies present a mixed picture, with some findings conflicting and others consistent, underscoring the need for a thorough review of the literature on green consumption. This study aims to assess the existing literature on green consumption by examining major theoretical frameworks, socio-demographic characteristics, and geographic contexts of green consumers, as well as the most studied product categories. It also explores the antecedents and consequences of green product purchases, the mediators and moderators affecting these relationships, and the methodologies used by scholars in this field. Methods Using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) and TCCM (Theory-Context-Characteristics-Methodology) frameworks, the study systematically searches, selects, and synthesizes relevant data, providing a comprehensive mapping of research. This approach allows for a critical evaluation of theoretical foundations, diverse contexts of green consumption, key variables, and the methodologies employed in previous studies. Results and discussion The findings indicate that social psychology theories are prevalent in green consumption research and highlight the need to expand the field’s theoretical base. By identifying underexplored product categories, socio-demographic groups, and geographic regions, marketers can more effectively target new segments. The review also identifies major enablers and barriers to green product purchases and suggests further investigation into underexplored variables to develop more effective marketing strategies. To advance the study of consumer behavior regarding green products, the review advocates for the use of mixed-method and qualitative approaches. This comprehensive approach is essential for gaining a deeper understanding of consumer behavior and improving strategies to promote green purchasing and enhance market penetration.